Divergent total synthesis of 1,6,8a-tri-epi-castanospermine and 1-deoxy-6,8a-di-epi-castanospermine from substituted azetidin-2-one (beta-lactam), involving a cascade sequence of reactions as a key step - Tiwari, Dipak Kumar; Bharadwaj, Kishor Chandra; Puranik, Vedavati G.; Tiwari, Dharmendra Kumar (Organic & Biomolecular Chemistry, 2014)
A divergent, short, and novel total synthesis of 1,6,8a-tri-epi-castanospermine (7) and 1-deoxy-6,8a-di-epi-castanospermine (8) has been developed via a common precursor, 15, obtained from D-mannitol derived beta-lactam. The key step involves a one pot cascade sequence of trimethyl sulfoxonium ylide based cyclization of epoxy sulfonamide 14 via epoxide ring opening, one carbon homologation followed by intramolecular cyclization.